Life in a day [videorecording (DVD)] - Scott, Ridley; Scott, Tony, 1944-2012; Macdonald, Kevin, 1967- (Virgil Films ; National Geographic Entertainment], 2011)
People from 192 countries submitted more than 80,000 videos to YouTube of personal events that happened in their lives on July 24th, 2010. Over 4,500 hours of contributed footage was sifted through to create this motion picture event.